Pengaruh Penggunaan Video Sentuhan Boleh dan Tidak Boleh terhadap Pendidikan Seks Anak - Safyana, Suci Indra; Marlina, Serli; Yaswinda, Yaswinda (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
The research haspirpose to determine the influence of the use of touch videos may and may not be on child sex education. The research method is Quarsi Experiment quantitative. The results of the study are that children in the experimental class who use touch videos may and may not have a higher number than the control class that uses images. The average number of experiment class 88,91 and 77,83 class control. Based on data analis is Ëƒ that is 2,256 Ëƒ 2,073. Thus it can be concluded that touch videos may and should not affect child sex education.